High-frequency and intrinsically stretchable polymer diodes - Matsuhisa, Naoji (2023)
Skin-like intrinsically stretchable soft electronic devices are essential to realize next-generation remote and preventative medicine for advanced personal healthcare1-4. The recent development of intrinsically stretchable conductors and semiconductors has enabled highly mechanically robust and skin-conformable electronic circuits or optoelectronic devices2,5-10. However, their operating frequencies have been limited to less than 100 hertz, which is much lower than that required for many applications. Here we report intrinsically stretchable diodes-based on stretchable organic and nanomaterials-capable of operating at a frequency as high as 13.56 megahertz. This operating frequency is high enough for the wireless operation of soft sensors and electrochromic display pixels using radiofrequency identification in which the base-carrier frequency is 6.78 megahertz or 13.56 megahertz. This was achieved through a combination of rational material design and device engineering. Specifically, we developed a stretchable anode, cathode, semiconductor and current collector that can satisfy the strict requirements for high-frequency operation. Finally, we show the operational feasibility of our diode by integrating it with a stretchable sensor, electrochromic display pixel and antenna to realize a stretchable wireless tag. This work is an important step towards enabling enhanced functionalities and capabilities for skin-like wearable electronics.